Increasing the Brand Awareness of Midtown Hotel Surabaya - Sitju Melinda Crishtine (Kata Kita: Journal of Language, Literature, and Teaching, 2018)
A promotional video is important because it would increase the brand awareness of a product or service for brand awareness is closely associated with promotional tool. The goal here is to promote and introduce the product or service of a business to the public. Midtown Hotel Surabaya is a 3 - star hotel strategically located at Basuki Rahmat Street No. 76, Surabaya. The problem of Midtown Hotel Surabaya is the lack of promotional tools, especially in the form of promotional videos. Additional revenue is expected to increase through the promotional video. The portrayal of the pleasant staying experience one will get in a night is contained in the promotional video of Midtown Hotel Surabaya. The delicacy of food and beverage, comfortable bedding, and fast booking access would be the main selling points of the hotel. The video can be displayed in hotel or wedding exhibitions and Youtube to attract public’s attention of Midtown Hotel Surabaya. Moreover, the video can also be utilized as a sales tool for the sales team on sales visits to companies who have not known about Midtown at all.